Neocordana gen. nov., the causal organism of Cordana leaf spot on banana - Hernandez Restrepo, Margarita; Groenewald, Johannes Z.; Crous, Pedro W. (Phytotaxa, 2015)
Cordana leaf spot of banana is shown to be associated with several species of a new genus described here as Neocordana gen. nov. Furthermore, Neocordana belongs to Pyriculariaceae (Magnaporthales) rather than Cordanaceae where the type species of Cordana, C. pauciseptata resides. Neocordana is established to accommodate Cordana musae, C. johnstonii, C. versicolor, and a previously undescribed species, N. musicola, which is morphologically and phylogenetically distinct. Neocordana species are found to be associated with leaves of Musa spp. (Musaceae) and Canna denudata (Cannaceae). Based on these results, Cordanaceae is best recognized in a separate order, established here as Cordanales ord. nov.